(S)‐[6]‐Gingerol inhibits TGF‐β‐stimulated biglycan synthesis but not glycosaminoglycan hyperelongation in human vascular smooth muscle cells. (27th March 2013) - Kamato, Danielle; Babaahmadi Rezaei, Hossein; Getachew, Robel; Thach, Lyna; Guidone, Daniel; Osman, Narin; Roufogalis, Basil; Duke, Colin C.; Tran, Van Hoan; Zheng, Wenhua; Little, Peter J.
Abstract: Objectives: ( S )‐[6]‐Gingerol is under investigation for a variety of therapeutic uses. Transforming growth factor (TGF)‐β stimulates proteoglycan synthesis, leading to increased binding of low‐density lipoproteins, which is the initiating step in atherosclerosis. We evaluated the effects of ( S )‐[6]‐gingerol on these TGF‐β‐mediated proteoglycan changes to explore its potential as an anti‐atherosclerotic agent. Methods: Purified ( S )‐[6]‐gingerol was assessed for its effects on proteoglycan synthesis by [ 35 S]‐sulfate incorporation into glycosaminoglycan chains and [ 35 S]‐Met/Cys incorporation into proteoglycans and total proteins in human vascular smooth muscle cells. Biglycan level was assessed by real‐time quantitative polymerase chain reactions and the effects of ( S )‐[6]‐gingerol on TGF‐β signalling by assessment of the phosphorylation of Smads and Akt by western blotting. Key findings: ( S )‐[6]‐Gingerol concentration‐dependently inhibited TGF‐β‐stimulated proteoglycan core protein synthesis, and this was not secondary to inhibition of total protein synthesis. ( S )‐[6]‐Gingerol inhibited biglycan mRNA expression. ( S )‐[6]‐Gingerol did not inhibit TGF‐β‐stimulated glycosaminoglycan hyperelongation or phosphorylation of Smad 2, in either the carboxy terminal or linker region, or Akt phosphorylation. Conclusions: The activity of ( S )‐[6]‐gingerol to inhibit TGF‐β‐stimulated biglycan synthesis suggests a potential role for ginger in the prevention of atherosclerosis or other lipid‐binding diseases. The signalling studies indicate a novel site of action of ( S )‐[6]‐gingerol in inhibiting TGF‐β responses.